EFFECTIVENESS OF PROBLEM POSING APPROACH IN REGARDS TO PROBLEM SOLVING ABILITY OF THE SENIOR HIGH SCHOOL STUDENTS IN LEARNING MATHEMATICS - Dita Aldila Krisma; Wahyu Setyaningrum (Universitas Negeri Yogyakarta, 2017)
This research aimed to find out the effectiveness of problem posing approach in regards to problem solving ability on high school students of class X in learning mathematics. This research was quasi experiment with pre-test post-test group design. The subjects of this study were students grade X in SMA Negeri Imogiri, where the samples were class X4. The samples were given the treatment of problem posing. The research instruments are problem solving ability test and observation sheet. The validity of the instruments was determined through content validity. The results of data analyze showed that learning by problem posing approach is effective to increase problem solving ability on high school students of class X SMA Negeri Imogiri in learning mathematics. Key words: effectiveness, problem posing, problem based learning, problem solving ability